Bukti Baru dari Indonesia: Perbedaan Lama Diare Pada Penderita Diare Akut yang Diterapi dengan Zink dan Probiotik Dibanding Probiotik di RSUD Dr. Moewardi Surakarta - Meneng, Putri (Jurnal Kedokteran Indonesia, 2009)
Background: Zinc supplementation reduces the duration of diarrhea, so does probiotic. Combination therapy of zinc and probiotic should reduce the duration of diarrhea more than probiotic alone. The aim of this study was to evaluate the difference of diarrhea duration between zinc-probiotic group and probiotic group.Methods: A randomized controlled trial was conducted at the pediatric ward Dr. Moewardi Hospital Surakarta, from April to July 2009. There were 64 subjects taken as the study population. Zinc and probiotic supplementation were given in experimental group and probiotic supplementation in control group. Both the subjects and the care providers were blinded. The data were analyzed by linear regression model.Results: Baseline characteristics were similar in both groups. Based on this study, there was shortening of diarrhea duration in experimental group as 1.8 days (b= -1.8; 95%CI -1.3 to -2.3).Conclusion: Combination therapy of zinc and probiotic reduces the duration of diarrhea in children. Jurnal Kedokteran Indonesia: 1 (1): 49-55Keywords: zinc, probiotic, acute diarrhea, randomized controlled trial.